Social Change and Educational Problems in Japan, Singapore and Hong Kong - Lee, W. author. aut Link
XV, 303 p.
Keywords: The spectacular economic and technological achievements of certain Far Eastern countries have attracted world wide attention. The markets of the West are dominated by the products of countries with no traditions of industrialisation and few natural resources. The reaction to this phenomenon has been a mixture of amazement, admiration, envy and, curiosity to know how it was done. This book addresses these questions through a study of the modernisation of three of the most successful Asian societies - Japan, Singapore and Hong Kong.